Beberapa Keunikan Linguistik Bahasa Madura - Akhmad Sofyan (Humaniora, 2007)
Linguistic items e.g. phonology, lexicon, and structure or word order in Madurese have uniqueness. Phonology uniqueness in Madurese consists of (1) type of phonem, (2) phonem combination, and (3) syllable pattern. Meanwhile Madurese lexicon uniqueness comprises: (1) no third person pronoun, (2) no plural first person pronoun, (3) no clitic, (4) the same symbol used both for 'nothing' and 'empty', (5) the use of auxilliary verb, and (6) the use of particle. Madurese alaso has uniqueness in its structure particularly in (1) reduplication, (2) passive construction, (3) possessive construction, (4) imperative construction, (5) comparative construction, (6) superlative construction, (7) 'acting like ...' construction, (8) morphophonemic prefix N-, and (9) the distribution of prefix N-.